Pengaruh Promosi Terhadap Kepuasan Pelanggan Di PT Electronic City Cabang Pamulang: INFLUENCE OF PROMOTION TOWARDS CUSTOMER SATISFACTION - Ibrohim; Agi Nugraha; Rizky dan Agi, Rizky hidayah (PRODI MANAJEMEN STIE MBI DEPOK, 2024)
This research was conducted from December 2022 to May 2023. The research objective was to generate information in the form of a more in-depth explanation about the influence of promotion on customer satisfaction and to obtain results from data processing on the extent of the influence of promotion on customer satisfaction. The method used was causality or cause-and-effect with the influence method. The type of research was descriptive and verificative with a population and sample of 95 customer respondents, using field studies and direct surveys through questionnaire distribution. The result of the simple linear regression equation between X and Y is Y=9.481+0.638+e. The results of Hypothesis Testing show that the Promotion variable has a sig value < 0.05, meaning it is significant. tcount=9.269 > ttable=1.6610. Thus, the Promotion variable has a positive and significant relationship with Customer Satisfaction. Therefore, the hypothesis test result: H1 is accepted and H0 is rejected. The correlation coefficient obtained is r=0.693, which means there is a strong and positive relationship indicating that an increase in Promotion can generally increase Customer Satisfaction. The result of KD (R²) = 0.480. This means that 48% of the independent variable, Promotion, can explain Customer Satisfaction. The remaining 52% is explained by other factors not examined in this study.